GAYA BAHASA KHUTBAH JUM’AT DI KOTA PALANGKA RAYA: Perspektif Filsafat Bahasa Biasa - Syairil, Fadli; Ade, Afriansyah; Nurlina, Nurlina (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The purpose of this article is to explore the language of Friday sermons at Al-Amin Mosque in Banturung, Bukit Batu District, Palu Raya, from the perspective of everyday language philosophy. This study uses an eclectic hermeneutic approach, which begins with a systematic process of data collection and separation. All collected data were then evaluated through several important elements, namely descriptive, interpretative, reflective, inclusive, and synthetic methods, to gain a deeper understanding of the object of study. The results of the study indicate that the language used in Friday sermons at Masjid Al-Amin is greatly influenced by the diversity of linguistic tools and their usage, as well as the variation in word types and sentence structures employed by the preacher. These findings were then compared with the views of logic experts on language structure, resulting in the conclusion that the language of Friday sermons at the mosque is a form of language play, namely religious language that has a special function in conveying moral and spiritual messages to the congregation. This study is expected to contribute to the development of the science of communication in preaching and serve as a reference for preachers in selecting and using effective language in conveying religious messages. This study emphasizes the importance of understanding the context and variety of language use in everyday religious preaching practices.